2005
DOI: 10.1007/s10511-005-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of OH megamaser galaxies in the radio continuum. I. Observational data

Abstract: Radio observations with the VLA-A radio telescope of 30 OH megamaser galaxies at a frequency of 1.49 GHz are discussed. Radio emission was detected from all 30 of these galaxies. Radio emission was detected from 5 of the 30 objects for the first time. Important results were obtained for 12 galaxies that had previously been little studied in the radio continuum. Additional data at 1.49 GHz were obtained for the remaining 13 objects. The core component of the continuum radio emission predominates in the OH megam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The properties of radio continuum emission, including spectral index and brightness temperature, can also be used to classify the central energy source of OHM galaxies (Kandalyan 2005a,b;Baan & Klöckner 2006;Sotnikova et al 2022). Kandalyan (2005a) and Baan & Klöckner (2006) obtained the radio structure of 30 and 51 OHM galaxies in the radio continuum based on VLA observations. They found that the OHM galaxies can be classified into different types, for instance, AGN and starburst-dominated sources.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of radio continuum emission, including spectral index and brightness temperature, can also be used to classify the central energy source of OHM galaxies (Kandalyan 2005a,b;Baan & Klöckner 2006;Sotnikova et al 2022). Kandalyan (2005a) and Baan & Klöckner (2006) obtained the radio structure of 30 and 51 OHM galaxies in the radio continuum based on VLA observations. They found that the OHM galaxies can be classified into different types, for instance, AGN and starburst-dominated sources.…”
Section: Introductionmentioning
confidence: 99%